Monitoring land changes at an open mine site using remote sensing and multi-spectral indices - Ikram Loukili; Ahmed Laamrani; Mustapha El Ghorfi; Saida El Moutak; Abdessamad ghafiri (Heliyon)
This study investigates the growth of mining activities in Benguerir, one of Morocco's largest and fastest-growing phosphate mines and a global leader in phosphate production, using remote sensing and ancillary data. The study examines spatio-temporal changes in land use and land cover (LULC) within this phosphate mining city to analyze the impacts of mining on agricultural areas, built-up lands, and water bodies over time. A series of images from 1984 to 2021 were processed in to assess patterns of change within the city. Five LULC maps were generated using supervised classification with the maximum likelihood method, providing detailed insights into both urban and non-urban transformations during the study period. Classification quality was evaluated using accuracy assessment and the Kappa index. Additionally, multi-spectral indices, including the Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), and Normalized Difference Built-up Index (NDBI), were simulated and analyzed across four intervals. The results reveal significant variations in LULC and ecological indices over time, which are associated with mining activities, water stress, urban sprawl, and socio-economic changes in the region.These results provide a valuable means for decision-makers and planners to effectively manage the spaces and lands in the future.